2017
DOI: 10.1088/1361-648x/29/16/163001
|View full text |Cite
|
Sign up to set email alerts
|

Polydomain structures in ferroelectric and ferroelastic epitaxial films

Abstract: A review of theoretical models, phase field modeling and experimental studies of domain structures in epitaxial films is presented. The thermodynamic theory of such domain structures is presented within the macroscopic thermo-mechanical framework. The theory allows for the evaluation of the main parameters of the domain structure using the energy minimization approach applied to the energy of elastic interactions. For homophase (polytwin) films, the thermodynamic theory provides a quantitative tool that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 109 publications
0
20
0
Order By: Relevance
“…[13] Also presence of domain walls can be identified, for [135]/[111] 28.56° PZT shown in Figure 2a, the marked region of c/c domain wall exhibit clear contrast of piezoresponse in 2a-d is that polydomain structure exhibit island like domain configurations, which is in contrast from the expected PZT tetragonal polydomain structure with regularly shaped domain variants based on c/a domain structure. [14] In single crystal PZT thin films, three domain variants c/a 1 /a 2 are normally observed in a cubic-tetragonal transformation, where c, a 1 , and a 2 are the domains that point along [001], [100], and [010], respectively. [14] Such type of regular polydomain structure can be controlled by varying substrate strain, film thickness, orientation, and composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Also presence of domain walls can be identified, for [135]/[111] 28.56° PZT shown in Figure 2a, the marked region of c/c domain wall exhibit clear contrast of piezoresponse in 2a-d is that polydomain structure exhibit island like domain configurations, which is in contrast from the expected PZT tetragonal polydomain structure with regularly shaped domain variants based on c/a domain structure. [14] In single crystal PZT thin films, three domain variants c/a 1 /a 2 are normally observed in a cubic-tetragonal transformation, where c, a 1 , and a 2 are the domains that point along [001], [100], and [010], respectively. [14] Such type of regular polydomain structure can be controlled by varying substrate strain, film thickness, orientation, and composition.…”
Section: Resultsmentioning
confidence: 99%
“…[14] In single crystal PZT thin films, three domain variants c/a 1 /a 2 are normally observed in a cubic-tetragonal transformation, where c, a 1 , and a 2 are the domains that point along [001], [100], and [010], respectively. [14] Such type of regular polydomain structure can be controlled by varying substrate strain, film thickness, orientation, and composition. [14][15][16][17] The typical expected polydomain structure based on misfit are two domain c/a/c/a stripe shaped, and three domain cellular or hierarchical (second-order) polydomain structures based on distribution of c and a domains.…”
Section: Resultsmentioning
confidence: 99%
“…Such a collective domain switching process is strongly related to the potential energy barrier between the two domain-structure variants. Based on Landau-type phenomenological theory for polydomain structures 38 , the calculated Landau free-energy densities of the a 1 / a 2 and c/a domain patterns are equal at the critical strain of ~0.46% at 300 K; however, at high temperature, such as 500 K, are about −22 MJ/m 3 and −19 MJ/m 3 , respectively, with an energy difference of only ~3 MJ/m 3 (Supplementary Fig. 13).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, 40-nm-thick, (001)-oriented films of PbTiO 3 grown on DyScO 3 (110) O (where the O denotes orthorhombic indices) experience a compressive strain that drives the formation of traditional c / a domain structures, while films grown on NdScO 3 (110) O substrates with large tensile strain exhibit a 1 / a 2 domain structures, and films grown on SmScO 3 (110) O substrates with a strain state between that of DyScO 3 and NdScO 3 exhibit a coexistence of both c / a and a 1 / a 2 domain variants 36 . In effect, epitaxial strain can be used to place this material on the brink of a transition between domain-structure variants and is an ideal route by which to explore the potential for large responses and collective effects 37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…a micron. [98] Finally, in the context of period doubling and tripling, Roytburd et al [98] have recently stressed in a comprehensive review on ferroelastics, that there may be situations in which two different kinds of domains are simultaneously present in quasi-equilibrium, due to boundary conditions, and these do not involve nonlinear doubling or tripling. And Jang's laboratory has shown that the Landau-Lifshitz-Kittel law can fail in nanostructures due to surface layers.…”
Section: Discussionmentioning
confidence: 99%